The complex relationship between diet, symptoms, and intestinal inflammation in persons with inflammatory bowel disease: The Manitoba Living With IBD Study. Issue 4 (23rd September 2021) - Dolovich, Casandra; Shafer, Leigh Anne; Vagianos, Kathy; Witges, Kelcie; Targownik, Laura E.; Bernstein, Charles N.
Abstract: Background: We aimed to examine whether an association exists between diet quality, based on the Prospective Urban Rural Epidemiology (PURE) Healthy Diet Score (HDS), and active inflammatory bowel disease (IBD). Methods: Participants were drawn from the Manitoba Living With IBD Study cohort. The Harvard Food Frequency Questionnaire (FFQ) was used to calculate the HDS at two time points: baseline and 1‐year follow‐up. Using generalized estimating equations (GEE) logistic regression, we assessed the association between the HDS and (1) the IBD Symptom Inventory (IBDSI); (2) intestinal inflammation, measured by fecal calprotectin (FCAL); and (3) self‐reported IBD flares. Results: There were 294 completed FFQs among 153 people. Of these, 100% had completed data about an IBD flare, 98% had FCAL measurements, and 96% had completed IBDSI scores. On a HDS scoring method of 0–8, the odds of FCAL >250 mcg/g were lower for participants with a HDS of 4 vs 0–3 (adjusted odds ratio [OR], 0.38; 95% CI, 0.19–0.77). When applying a second HDS scoring method (8–40), the odds of having an IBD flare were 3.6 times greater with a HDS between 21 and 24 compared with an HDS ≤20 (adjusted OR, 3.63; 95% CI, 1.03–12.78). Conclusions: We found that active inflammation was less likely among those with a moderate HDS, whereas symptomatic IBD flares were more likely. People may choose to consume a moderate amount of healthy foods such as fruits and vegetables, even knowing that those foods may cause a symptomatic flare.